Pigott’s Private Eye: Radicalism and Sexual Scandal in Eighteenth-Century England - Rogers, Nicholas (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1993)
AbstractCharles Pigott hailed from a Shropshire gentry family that made the transition from Jacobitism to Jacobinism in the eighteenth-century. A bon vivant and man of the turf, Pigott scandalised the establishment by exposing the decadent habits of the landed aristocracy in the Jockey Club and the Female Jockey Club. These scurrilous exposés brought Pigott fame and persecution; they also established him as one of the first radical writers to make political capital out of the "boudoir politics" of the aristocracy.This paper examines the language of defamation in these pamphlets, their antecedents and their political purchase. Although the Jockey Club proved a resounding success, its sequel was less so; and this fact raises the question of why sexual scandal ultimately proved a more potent weapon of political criticism in late-eighteenth century France than in Britain. One reason is related to Britain's counter-revolution, to the reaction of the propertied classes towards French revolutionary violence, however critical they may have been to aristocratic libertinism. But another has to do with the nature of political society in France, the closer articulation between the “noble body” and the body politic. In Britain's more pluralist society, dominated by Parliament rather than the Court, attacks on the morals of the aristocracy were less politically damaging than they were in the France of the ancien regime.